The Effect Of Tax Management, Bonus Mechanism And Foreign Ownership On Transfer Pricing Decision - Diah Fitri; Nur Hidayat; T. Arsono (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2019)
The objective of this research isto prove and explain The Effect Of TaxManagement, Bonus Mechanism And Foreign Ownership On Transfer Pricing Decisionpartially and simultaneously. This researchused purposive sampling criteria and logistic regression analysis test. Total sample 76 companies listed in the Indonesia Stock Exchange (BEI) during 2012-2014. The result showed that tax management have a positive impact and significant on Transfer Pricing Decision. Bonus mechanismhave a positive impact and significant on onTransfer Pricing Decision, Foreign Ownershiphave a positive impact and significant on onTransfer Pricing Decision and all these variables effect simultaneously on Transfer Pricing Decision